`We too will have to wait a year`: The impacts of COVID-19 and the postponement of the Tokyo 2020 Paralympic Games from Brazilian athletes and coaches` perspectives - Martins Patatas, J.; Winckler, C. (Sport in Society: Cultures, Commerce, Media, Politics, 2022)
The COVID-19 outbreak resulted in the postponement of several sporting mega-events. However, research investigating the direct impacts on Paralympic sport is sparse. This study explored how Brazilian Paralympic athletes and coaches perceived the potential impacts on training and sport performance as consequences of the complexities surrounding the COVID-19 outbreak and the postponement of the Tokyo 2020 Paralympic Games. A convergent parallel mixed-methods design was used, and an online survey was applied to collect quantitative data with Paralympic athletes (n = 93) while national coaches (n = 12) participated in semi-structured interviews. Results indicated that the perception of the participants converged concerning the impact on training conditions. Their perceptions diverged concerning the impact on athletic performances at the Paralympics, where coaches believed in drop in performances, while athletes seemed confident or indifferent. The inferences gained reinforce the need for more actions that actively engage in minimising the lack of representation and visibility of Paralympic sports.